SEJARAH PENDIDIKAN ISLAM DI KALIMANTAN BARAT - Irmayanti (CBJIS : Cross-Border Journal of Islamic Studies, 2021)
This study aims to analyze the history of the entry of Islam in Kalimantan and Islamic educational institutions in West Kalimantan before and after independence. This research method uses a literature review. The primary data source is the history book of Islam in Kalimantan. Secondary data sources use references to journals, books, and magazines relevant to this research study. The results of this study indicate that the entry of Islam into West Kalimantan is not known for certain, there are still many differences of opinion from various groups, including that Islam first entered West Kalimantan in the 15th century, and there is also an opinion that Islam entered West Kalimantan in the 15th century. 16. The first areas in West Kalimantan that were previously thought to have received a touch of Islam were Pontianak, Matan, and Mempawah. Another center for the spread of Islam in West Kalimantan is near Muara Sambas. It is estimated that Islam entered this area in the sixteenth century brought by people from Johor, following later the kingdom of Johor conquered the Sambas area. Islamic education in Kalimantan was pioneered by Madrasatun Najah wal Falah, founded in 1918 AD, and this became the inspiration for establishing other Ibtidaiyah and Tsanawiyah madrasas. Among them are: Islamic College Madrasah (Assulthaniah) in Sambas, Al-Raudlatul Islamiyyah in Pontianak, Junior Islamic High School (SMIP) in Banjarmasin, Amuntai Islamic Normal Madrasa, and many other madrasas, such as Imad Darussalam in Martapura, Middle School Islam in Kandangan, Al-Ashriah in Banjarmasin and others. The Islamic educational institutions in West Kalimantan before independence consisted of Madrasahtun Najah Walfalah, Madrasah As-Sultaniyah Sambas and Pontianak Islamic College. After independence consisted of the 50s Era (Madarsah Diniyah Ismail Mundu, Waqf Board al-Madrasah al-Arabiyah Islamiyah (BAWAMAI) Pontianak, Pontianak Muhammadiyah SLPT Educational Institutions), the 70s Era (Ponpes: Development of Ushuluddin Singkawang, Darul Ulum Pontianak, Baisuni Imran Sambas), the 80s (Mujahidin College, Salafi As-Salam Islamic Boarding School, Al-Falah Islamic Center Foundation, Islamic Education Institution MTs Al-Ma'arif NU Pontianak, and Baitul Atik Ketapang Islamic Boarding School), 90s Era (Ponpes ; Al-Jihad Hulu Gurung (Kapuas Hulu), Darussalam Sekubang (Mempawah), Al-Ma'arif NU Sintang, Khulafaurrasyidin (Pontianak), and Matala'u Anwar (Pontianak).